When things fall apart: Separation and divorce among adolescents and young couples in Ethiopia - Author, EYL; Pankhurst, A; Crivello, G (Young Lives, 2020)
While there is rightly a major focus on child marriage, we know very little about separation and divorce among young couples, either in Ethiopia or elsewhere. How do they negotiate their relationships? What contributes to relationship breakdown? What access do they have to support and services? And what happens after they separate?